Cloning and Expression of a Truncated Form of the p72 Protein of the African Swine Fever Virus (ASFV) for Application in an Efficient Indirect ELISA System - Julieta Sandra Cuevas-Romero; Perla Lucero Zavala-Ocampo; Sonia Pina-Pedrero; Llilianne Ganges; Adriana Muñoz-Aguilera; José Bryan García-Cambrón; Fernando Rodriguez; Aruna Ambagala; José Luis Cerriteño-Sánchez (Pathogens)
African swine fever (ASF) is a disease that affects both domestic and wild swine. It was recently reported in the Dominican Republic and Haiti (2021), representing a substantial risk to America. The goal of this study was to produce a truncated form of the ASF-p72 recombinant protein based on the ASF strain genotype II (Georgia 2017) as well as to develop and validate a sensitive and specific ASF indirect-ELISA (iELISA) for early detection of ASF. The truncated ASF-p72 recombinant protein was successfully expressed in E. coli BL21/DE3 cells using the pET-SUMO plasmid. Bioinformatics analysis showed 100% homology among the new isolates of ASFV from genotype II. The ASF-p72-truncated protein was used to develop an iELISA, which had a high sensitivity (88%) and strong specificity (97%); the concordance index kappa was K = 0.872, indicating nearly perfect agreement compared to the WOAH confirmatory immunoperoxidase test. The validation results utilizing the reference sera panel from the OIE-ASF Reference Laboratory show the excellent detection capabilities of ASF antibodies up to a 1:1000 serum dilution. The inter-assay coefficient of variation (CV 10.4%) and intra-assay CV (2.8%) data show that the assay is precise and reproducible. This biotechnology advancement can be used to conduct future epidemiological research for ASF surveillance in ASF-free American countries.